Sex & relationships in trans people. (February 2023) - Kennis, Mathilde; Kreukels, Baudewijntje P.C.; Dewitte, Marieke
Abstract: Everyone has sexual rights and is entitled to enjoy sex, regardless of gender identity or expression. It is therefore encouraging to witness a recent growth in research on sexuality in transgender individuals. We provide a short overview of extant research on sex and relationships in this population and argue that current research has mostly been conducted from a medical and functional approach; there is a strong focus on negative experiences and prevention; and there is a lack of data regarding psychological and socio-relational variables. Furthermore, many studies have been conducted in a cis- and hetero-normative setting and have methodological shortcomings such as applying questionnaires that have not been validated in a transgender population. We encourage researchers to expand their focus to positive variables such as sexual pleasure and (in accordance with the biopsychosocial model) investigate subjective experiences and relationship variables when studying sexuality in transgender individuals. Highlights: Sexuality in trans individuals has mainly been approached from a functional framework. Most research has been conducted in a cis- and heteronormative context. Studies should also focus on psychosocial factors and outcomes. Next to negative outcomes, researchers should study positive experiences. Researchers should consider the relational setting in which sex often occurs.